2022
DOI: 10.1097/bsd.0000000000001412
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Parameters in Cervical Myelopathy

Abstract: Study Design: This was a narrative review. Objectives: Provide a comprehensive review of radiographic alignment parameters and their effect on procedure selection, surgical decision-making, and clinical outcomes for the treatment of cervical spondylotic myelopathy (CSM). Summary of Background Data: The use of radiographic parameters to predict prognosis and surgical outcomes in patients with CSM is an evolving field given the complex presentation of patients with this condition. Methods: A literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Wang et al [ 29 ] demonstrated that decreased T1 slope postoperatively prevented the cervical spine to tilt forward by regulating C2-7 SVA, and facilitates the neurological recovery. In surgical planning and decision-making, the utilization of key radiological parameters can allow surgeons to optimize clinical outcomes for CSM [ 30 ]. In this study, we observed that after CLK was corrected, the C2-7 Cobb angle was restored, and the T1 slope and C2-7 SVA were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 29 ] demonstrated that decreased T1 slope postoperatively prevented the cervical spine to tilt forward by regulating C2-7 SVA, and facilitates the neurological recovery. In surgical planning and decision-making, the utilization of key radiological parameters can allow surgeons to optimize clinical outcomes for CSM [ 30 ]. In this study, we observed that after CLK was corrected, the C2-7 Cobb angle was restored, and the T1 slope and C2-7 SVA were increased.…”
Section: Discussionmentioning
confidence: 99%